Analysing a Chemistry Lesson on Ionic Bonding: Insights from a Learning Study - Andrew, Vincent; Hj Sabli, Hjh Rosinah (SEAMEO QITEP in Science, 2024)
The aim of this paper is to report the insights gained from analysing an online Chemistry lesson on ionic bonding as part of a learning study conducted during the COVID-19 pandemic in 2021. The lesson was collaboratively developed by a group of seven high school Science teachers supported by two facilitators. Data collected includes the lesson plan, the transcript from the virtual lesson, and teacher reports. Insights were drawn from each phase of the learning study cycle – Study, Plan, Teach, Reflect. In the Study phase, the teachers came up with several presumed critical aspects based on responses to a two-part pre-test. In the Planning phase, a pattern of variation was used. In the online Teaching phase, we found potential critical aspects emerged when the students interacted with the object of learning, but this was not picked up by the teacher. The critical aspects identified from the learners’ point of view include the number of shells for each atom and the number of electrons in each shell. In the Reflect phase, we consider the role of facilitators in guiding the lesson to focus on the discernment of critical aspects. The insights gained can potentially support teachers on how to plan and analyse lessons using the variation theory of learning, particularly in the context of online teaching.